ASPECTS OF TREATMENT OF JUVENILE ARTHRITIS WITH SOLUBLE RECEPTORS TO TNF - E.I. Alexeeva; S.I. Valieva; R.V. Denisova; T.M. Bzarova (Вопросы современной педиатрии, 2008)
The theme of review is the results of treatment of rheumatic diseases in adults and children with blocker of TNF-α etanercept. The data from single, open-labeled and multicenter double blinded placebo-controlled studies of activity and safety of etanercept is presented in this article. The results of researches show high efficacy of etanercept in treatment of rheumatoid arthritis and ankylosing spondylitis in children and adults. Besides high activity etanercept is one of the safest blockers of TNF-α in pediatric and adult practice.Key words: children, juvenile rheumatoid arthritis, treatment, etanercept.